Methods of developing a competitive strategy of the agricultural enterprise. Issue 2 (August 2019) - Tynchenko, V S; Fedorova, N V; Kukartsev, V V; Boyko, A A; Stupina, A A; Danilchenko, Yu V
Abstract: This article examines the features of the use of various strategies, as the basis for creating a competitive advantage of an agribusiness with stable positions both for entry and for keeping a high level during various financial changes in a market economy. Developed or selected strategy should be based on a comprehensive analysis of the business with strengths and weaknesses. The distinction between the strengths and weaknesses of a business, and accordingly the grouping of its features into advantages and disadvantages, allows them to be more accurately taken into account when choosing a strategy that provides competitive advantages. The reasons for the poor viability of various business aspects are the lack of development and the validity of strategies that reduce both the competitiveness and profitability of various enterprises. The given structure of strategies and their correct modernization in business will make it possible to enhance the stability of the presence of an enterprise afloat of financial success. Competitive advantages of a business are the advantages manifested in the position of the firm in the market, which is more advantageous in relation to competitors and is achieved using methods and tools of strategic planning that take into account the characteristics of small business.